2018
DOI: 10.4103/ijpsym.ijpsym_368_17
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week Comparative Prospective Open-label Randomized Controlled Study in Depression Patients Treated with Vilazodone and Escitalopram in a Tertiary Care Hospital in North India

Abstract: Background: Depression is a leading cause of morbidity in modern world and introduction of selective serotonin reuptake inhibitors (SSRIs) was a revolution for treating depression. However, sexual dysfunction and weight gain always remained an issue for patients leading to discontinuation of treatment. Vilazodone is a novel SSRI and literature show better efficacy and decrease weight gain and sexual dysfunction. Aim of study: This study aims to compare the efficacy, sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The common side effects of VLZ include nausea, diarrhea, and headaches, which are also common for other SSRIs. In contrast, VLZ is not as frequently associated with a reduction in sexual dysfunction [49][50][51] , the most common cause of discontinuation of SSRI treatment 52 . Also, weight gain is reduced with VLZ treatment relative to other SSRIs [49][50][51] .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The common side effects of VLZ include nausea, diarrhea, and headaches, which are also common for other SSRIs. In contrast, VLZ is not as frequently associated with a reduction in sexual dysfunction [49][50][51] , the most common cause of discontinuation of SSRI treatment 52 . Also, weight gain is reduced with VLZ treatment relative to other SSRIs [49][50][51] .…”
mentioning
confidence: 94%
“…In contrast, VLZ is not as frequently associated with a reduction in sexual dysfunction [49][50][51] , the most common cause of discontinuation of SSRI treatment 52 . Also, weight gain is reduced with VLZ treatment relative to other SSRIs [49][50][51] . However, despite these intriguing properties, the molecular basis for VLZ binding to SERT remains an open question.…”
mentioning
confidence: 94%
“…1 In a 12-week comparative prospective open-label randomized controlled study in depression patients treated with vilazodone and escitalopram, Manish Bathla et al, 2018 reported that more females were receiving treatment as compared to males, which is in agreement with our results. 14 The HAM-D scores calculated during the study were significantly lowered by vilazodone and escitalopram (P < 0.001). On intergroup comparison using independent t-test, vilazodone was found to cause more lowering of HAM-D score than escitalopram (P < 0.02).…”
Section: Discussionmentioning
confidence: 84%
“…13 In a 12-week comparative prospective open-label randomized controlled study conducted in north India comparing the efficacy and safety of escitalopram and vilazodone in MDD, vilazodone has been found to have better efficacy, lesser weight gain, and lesser sexual dysfunction. 14 Kudyar P et al reported that escitalopram was more efficacious and better tolerated than vilazodone in patients with MDD. 8 This observational study is undertaken with the aim to assess the effectiveness and side effects of vilazodone and escitalopram in patients diagnosed with major depressive disorder.…”
Section: Introductionmentioning
confidence: 99%
“…An open label randomized controlled study in depression showed that for the patient treated with vilazodone the ASEX score at 12 weeks was 11.73±3.55 (in this study ASEX total score were 14.63±1.33 at 8 week). 17 In another study conducted on the effect of sertraline on sexual functioning in patients with major depressive disorder the ASEX total score at baseline was 19. 13 A study on treatment emergent sexual dysfunction related to antidepressants shows that sertraline has higher rate of sexual dysfunction such as sexual desire, sexual arousal.…”
Section: Asex-total Adjusted Scorementioning
confidence: 99%